The critical pharmaceutical situation in Sudan 2023: A humanitarian catastrophe of civil war - Lina Hemmeda; Angad Tiwari; Barakat Olajumoke Kolawole; Fathima Shehnaz Ayoobkhan; Kainat Fatima; Moshi Moshi Shabani; Mrinmoy Kundu; NagaSpurthy Reddy Anugu; Riya Mary Richard; Danya Ibrahim; Khabab Abbasher Hussien Mohamed Ahmed (BMC, 2024)
Abstract The situation in Sudan have deteriorated since the ongoing war outbreak in April 2023. This article sheds light on the pharmacological status in Sudan in terms of shortage of supply, rising demands, and regulatory issues. The ongoing civil war has acutely impacted the dilapidated pharmaceutical status of Sudan, patients have suffered from the paucity of medical services forcing an out-of-control rise in underreported morbidity and mortality. To mitigate this uprising issue, an increase in stakeholder communication is crucial to deal with this national threat and establish a system for reporting the shortage.